The effect of grazing systems on livestock and vegetation. A comparison of different methods of managing bluestem pastures. - Smith, E.F.; Anderson, K.L.; Baker, F.H. (Kansas Agricultural Experiment Station, 2012)
Good quality Hereford yearling steers weighing approximately 565 pounds were used to stock the pastures. The method of management of each pasture was as follows: Pasture 1-Normal rate of stocking, 3.75 acres per head. Pasture 2-0verstocked, 2.74 acres per head. Pasture 3-Understocked, 5.45 acres per 'head. Pastures 4, 5, 6-Deferred and rotation grazing, 3.75 acres per head. All the steers were held in two pastures until June 30, then turned into the protected pasture until August 3. On that date they were placed on the better of the two pastures previously used, where they remained until August 10. After that they were allowed the run of all three pastures. Pasture 7-Burned March 13, 1953; rate of stocking was 3.67 acres per head. Pasture 8-Burned April 9, 1953; rate of stocking was 3.67 acres per head. Pasture 9-Burned April 30.1953; rate of stocking was 3.67 acres per head.
Keywords: Beef; Grazing systems; Stocking rates; Deferred grazing; Burning; Gains